A presença da cultura afro-brasileira na fronteira da cidade de Foz do Iguaçu - Paraná - Brasil - Guimarães, Jarbas da Silva (2021)
The present dissertation addresses the presence of Afro-Brazilian cultural representations on the border and their symbolic expression within the social system in the city of Foz do Iguaçu - Paraná - Brazil. It aims to comprehend and analyse the presence of Afro-Brazilian Culture on the Border of the City of Foz do Iguaçu, when it comes to the social and mystical representations of the religious system, its rituals, its cultural and social communication process. And, as for specific objectives, it follows: a) to characterize the presence of the Afro-Brazilian culture; b) to present a brief history regarding the Afro-Brazilian religious culture, and c) to show the social integration and religiosity of an Afro-Brazilian matrix. The present work follows the steps of bibliographic and descriptive research. In addition to such, field research is used in order to obtain information with regards to religious leaders, houses of religious services and public entities which collaborate so that the Afro-Brazilian culture is disseminated in the city of Foz do Iguaçu. It is anchored in bibliographic, documentary, photographic and field collection records. In the first chapter, an approach is presented on the conceptions and the concept of Brasility (“Brasilidade”) for the construction of identity. In the second chapter of this research, Afro-Brazilian culture and its social and religious influence are demonstrated. In the third chapter, one will find a brief history of religious culture, the origin of Umbanda, syncretism and religious miscegenation and, finally, in the fourth chapter, religious manifestations in the Iguaçu society are presented. As a final consideration, the perception and presence of Afro-Brazilian culture are brought, manifested in cultural references such as music, gastronomy, clothing and, mainly, religious representations.